Study on RBC Count and Hb level between Bangladeshi and Kashmiri Medical Students of Khwaja Yunus Ali Medical College - Yasmin, Ayesha; Alo, Kamrunnahar; Sultana, Sabera; Yesmin, Laila (KYAMC Journal, 2020)
Background: Among the different blood parameters the total RBC count and blood hemoglobin level is important for the diagnosis of anemia. The results vary in different nations for environmental conditions and different dietary habits. Objectives: This study was to observe the total RBC count and blood Hb level in between the Bangladeshi and Kashmiri students of same age group. Dietary chart was also studied in between the two nationalities of students to observe any alteration of the result or not. Materials and Methods: This random study was done in Khwaja Yunus Ali Medical College, Sirajganj, Enayetpur on September, 2019. Total 200 students were included with specific age range, sex and diet history. The students were divided as 100 male and 100 female students. Total RBC count was estimated by fluid dilution (Dacie's fluid) method and Hb level was estimated by Sahli's acid hematin method. Results: Among 200 students, 94% Bangladeshi male and 98% Bangladeshi female and among Kashmiri's 96% male and 94% female students were in age between 19 to 21 years. Total RBC count>5million/cumm of blood was found in 24% Kashmiri and 08% Bangladeshi male students. Total RBC count in between 4M/cumm to 5M/cumm was present in 84% and 94% of Bangladeshi male and female students respectively and among 76% Kashmiri male and 90% Kashmiri female students. Hemoglobin level >15gm/dl was found among 54% Kashmiri and 10% Bangladeshi male students. It was alo observed that Kashmiri students were more habituated to protein rich diet than the Bangladeshi students. Conclusion: Present study revealed that environment and diet habit has an impact on alteration of total RBC count and blood Hb level. KYAMC Journal Vol. 11, No.-1, April 2020, Page 32-35